Բուսական տարրերը հայկական միջնադարյան եկեղեցիների արտաքին հարդարանքում - Ավետիսյան, Թագուհի
An important part of the exterior decoration of the medieval Armenian churches are plant motifs such as acanthus, palmettes, olive tree, lily, the Tree of Life etc., which are widespread both on the monuments of the Early Christian peri-od (Bayburd [5th -6th cc.], Kasakh [late 5th c.], Tekor [the 80s of the 5th c.], Ere-ruyk [6th c.] and others) and the churches of the High Middle Ages (The Holy Cross of Aghtamar [915-921], Ishkhan and Oshkvank [late 10th c.], Holy Apostles in Ani [10th-11th cc.], Tejaruyk [late 12th c.), St. Gregory [Tigran Honents‘] in Ani and John the Baptist in Gandzasar [13th c.]). These decorative motifs, having originated in the Pre-Christian (Ancient Eastern, Classical, and Hellenistic) epochs, were later revised, newly interpreted, and widely used in Christian, including Ar-menian, art. Важным составляющим внешнего убранства армянских средневековых церквей являются растительные мотивы, такие как аканф, пальметта, оливковое дерево, лилия, Древо жизни и др., нашедшие широкое распространение как на памятниках раннего периода (например, Байбурд (V-VI вв.), Касах (кон. V в.), Текор (80-е гг.V в.), Ереруйк (VI в.) и т.д.), так и в эпоху зрелого средневековья (например, церковь Св. Креста на острове Ахтамар (915-921 гг.), Ишхан и Ошкванк (обе втор. пол.X в.), Св. Апостолов в Ани (X-XI вв.), Тежаруйк (кон.XII в.), Св. Григория (Тигран Оненц) в Ани и Иоанна Предте-чи в Гандзасаре (обе XIII в.)). Отмеченные декоративные элементы восходят к дохристианской – древневосточной, античной и эллинистической – культуре и, подвергаясь переосмыслению и новой интерпретации, продолжают широко применяться в средневековом, в том числе, в армянском искусстве.
Keywords: Արևելաքրիստոնեական արվեստ; Բուսական զարդատարրեր